Fragmentos Do Feminino: Estilhaços, Metamorfoses E Alegorias No Cinema Sul-Americano - Ribeiro, Josiane Valcarenghi (2024)
The research presents reflections and analysis involving the representation of women in the cinematic works of Argentina, Brazil, Chile, Paraguay, and Uruguay, aiming to address the question of how women are depicted in the aforementioned film productions. The overarching goal is to propose the hypothesis that the representation of femininity in contemporary South American cinema is tied to a shared history of oppression and resistance, using allegory as a tool intersection of this common past. Allegory is employed as a means to explore the complexities of female experience, exposing both oppression and resistance to patriarchal and colonial structures. Furthermore, these representations transcend the male gaze, challenging hegemonic narratives and dismantling colonial frameworks by reclaiming marginalized voices and perspectives. The thesis seeks to integrate discussions on gender, cinematic narrative, decoloniality, patriarchy, and machismo to analyze how South American cinema portrays women. Women cease to be mere supporting characters and emerge as protagonists, challenging and reconstructing preconceived notions about their roles in society from an allegorical perspective. To achieve this objective, the research is grounded in the theoretical foundations of Maria Lugones, incorporating the contributions of Walter Mignolo and Aníbal Quijano to the discourse on decoloniality and gender in South America. Discussions on “allegory” draw upon Jeanne-Marie Gagnebin, complemented by Walter Benjamin and Ismail Xavier. For the analysis of narratives and characters in South American cinema, Robert Stam serves as a primary reference. Additionally, the study seeks to integrate South American theorists to strengthen its theoretical framework without excluding other relevant sources. This research is positioned within Comparative Studies, characterized by an analytical and inter-art comparative nature, employing bibliographical and qualitative approaches. A comparative method is used to analyze the films Aquarius (2016) by Kleber Mendonça Filho (Brazil), La Ciénaga (2001) by Lucrecia Martel (Argentina), Gloria (2013) by Sebastián Lelio (Chile), Las Herederas (2018) by Marcelo Martinessi (Paraguay), and Mi Amiga del Parque (2015) by Ana Katz (Argentina/Uruguay). This investigative process seeks to find a convergence point that does not impose rigid certainties about the representation of South American women but rather fosters a flexible perspective on the multiple possibilities of being. The study explores how the image of these women occupies a space still marked by colonial conditions and the imposition of external standards.